Pengaruh Promosi Dan Harga Dalam Meningkatkan Nilai Penjualan Minyak Kelapa Sawit Pada PT. PP Kwala Simpang, Aceh Timur - Amiruddin Idris (JURNAL AGRICA, 2018)
This study aims to analyze the effct of promotion and Price-to-sales of palm oil in PT. PP Kwala Simpang. Samples were taken in 2005 to 2010 (per semester) . The data collected through the techniques required documentation. The data analysis technique used is multiple linear regression analysis. Base don the results of the discussion in mind the value of F at 152.59 with a significance leve log 0.000, so that H1 is accepted and H0 is rejected. That is promotions and prices simultaneously have a significantce effect on the value of sales of palm oil in PT. PP Kwala simpang, can be accepted at a sigficance level of 5 percet. Tcount 10,104 for promotion with a significance level of 0,000, so that H1 is accepted and H0 is rejected. That is the promotion of a positive and significant effect on the value of the partial sale of palm oil in PT. PP Kwala Simpang, can be accepted at a significance level of 5 percent. T – test value for the Price of – 4.160 with a significance level of 0.002, so that H1 is accepted and H0 is rejected. That is, the Price significantly and negatively related to the value of partial sale of palm oil in PT PP Kwala Simpang, can be accepted at a significance level  of 5 percent. Value of the correlation coefficient (R) of 0.886, meaning that the promotion and the Price has a strong relationship with the sales value of palm oil in PT. PP Kwala Simpang. Valeu of the determinant coefficient (R Square) of 0.784, meaning that the value of sales of palm oil can be explained by promotions and prices by 78.4%, while 21,6% were 21,6% were explained by other factors, such as product and distribution channels. Keywords : promotion, Price, value of sales